Unveiling the Path: Organizational Trust, Social Relationships, and Their Impact on Organizational Citizenship Behavior at CV Hanselia - Susanto (Yayasan Bina Bisnis Nusantara Medan, 2025)
This research investigates the influence of organizational trust on organizational citizenship behavior (OCB) via social ties at CV Hanselia. This study utilizes data collected from questionnaires administered to 48 workers of CV Hanselia, which were subsequently evaluated using the Structural Equation Modeling (SEM) approach. The findings indicate that organizational trust positively influences organizational citizenship behavior, with social relationships serving as a reinforcing factor. These results show how important it is for people in an organization to trust each other and have excellent social ties to increase OCB and, in turn, help the business do better. The management implications of this study indicate that Hanselia CV should concentrate on formulating policies that enhance a culture of trust and social relationships among employees to foster positive behaviors that influence organizational performance and sustainability